(untitled) (ENTHYMEMA, 2023)
This contribution reviews Eccessi d’autore. Retoriche della voce nel romanzo italiano di oggi (Mimesis, Milano-Udine 2020), then dialogues with it by expanding the discourse to some issues which the book hint at, or implies.